TRIGONELLA FOENUM : A REVIEW OF HYPOGLYCEMIC ACTIVITY - Suryawati Suryawati; Safrida Safrida; Firdausa Sarah; Azizah Vonna; Vera Dewi Mulia (Universitas Syiah Kuala, 2019)
Treatment of diabetes mellitus is intended to reduce the risk of blindness, kidney failure, neuropathy and heart disease that can develop due to the chronic increase in the blood glucose level. The selected hypoglycemic agents should be effective, safe and readily available. The widely used agents work by interrupting enzymes responsible for glucose regulation. Those enzymes are α-amilase, α-glucosidase, dipeptidyl peptidase-IV, aldose reductase and angiotensin converting enzyme. A medicinal plant, fenugreek (Trigonella foenum-graecum) has been used as an antidiabetic folk medicine. This review provides information related to in vitro studies showing antihyperglycemic activity of fenugreek along with an in vivo study in animals. In addition, potential phytochemicals that have been isolated from this plant are described and play a role in the searching for the most potent agents for diabetes mellitus therapy.